Corundum mullite composite ceramic roller and preparation method thereof

By controlling the crystal form and microstructure, the ratio of alumina and silicon oxide is improved, the ratio of mullite is increased, and the crystal form control agent is used to improve the thermal shock resistance and strength of the ceramic roller rod, which solves the problem of the head and tail during sintering. Small problems have achieved efficient production and long-life use of ceramic roller rods.

CN119430876APending Publication Date: 2025-02-14JIN GANG NEW MATERIALS +1

Patent Information

Application Number
CN202411421700.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the sintering process, ceramic roller rods are prone to problems with large heads and small tails, which affects the strength and use effect. At the same time, when traditional corundum mullite roller rods improve thermal stability, the mullite strength is low, affecting the overall strength.

Method used

By controlling the crystal form and microstructure, improve the ratio of alumina and silicon oxide, increase the ratio of mullite, and use crystal form control agents such as boron oxide and magnesium fluoride to prevent abnormal growth of grains, improve conversion and heat resistance Shock. The preparation method of combining extrusion and cold isostatic pressure is adopted to improve the density of the blank, and the high flexural strength and good thermal shock resistance of the ceramic roller rod are achieved through specific firing technology.

Benefits of technology

The diameter uniformity of ceramic roller rods is achieved, the overall strength and thermal shock resistance of the roller rods are improved, the service life is extended, the equipment maintenance cost is reduced, and the production efficiency is improved and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430876A_ABST
    Figure CN119430876A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic rollers, and discloses a corundum mullite composite ceramic roller and a preparation method thereof, and the ceramic roller comprises the following components by weight: 30-60 parts of alumina micro powder, 1-40 parts of kaolin, 1-40 parts of corundum sand, 5-15 parts of a binder, and 2-6 parts of a crystal form control agent. According to the corundum-mullite composite ceramic roller prepared by the preparation method disclosed by the invention, by optimizing a crystal phase structure and combining an isostatic pressing technology process and conical design with hanging burning, better thermal shock resistance and bending strength are obtained, the wall thickness is relatively low, the dimensional deviation is smaller, and the requirements of a wide-body kiln with an ultra-long roller can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic rollers, and in particular to a corundum-mullite composite ceramic roller and a preparation method thereof. Background Art

[0002] Kilns play an important role in the industrial system, such as roller kilns, which can achieve high-efficiency, low-cost continuous operation. Ceramic rollers are one of the key components of roller kilns and are directly related to equipment performance and efficiency. Alumina ceramic rollers have good oxidation resistance, mechanical strength, thermal stability and wear resistance, etc., and have a wide source of raw materials and low production costs. They are widely used in the support and rolling devices of roller kilns. Because the corundum and mullite in the corundum-mullite alumina ceramic rollers are staggered and stacked, they have high bending strength, high wear resistance and good thermal shock resistance, and are often used in medium and high temperature areas of roller kilns. In the face of the need to reduce costs and increase efficiency, the width of roller kilns continues to increase, and the load increases. Therefore, as the load-bearing ceramic rollers, they must continuously improve their own strength, while ensuring that the thermal shock meets the requirements, especially the sintering of lithium battery raw materials is loaded in saggers and fired in roller kilns, and the load is significantly higher than that of ceramic plates. The following specific problems exist:

[0003] (1) The ceramic rollers are sintered by hanging firing. The traditional hanging firing method causes uneven fire control and temperature differences, resulting in a larger head and smaller tail of the rollers. This affects the strength of the rollers and affects the use of customers, which can easily cause the bricks to skew.

[0004] (2) In order to improve thermal stability, the traditional corundum mullite roller increases the proportion of mullite, and the strength of mullite is relatively low, which affects the strength of the roller. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a corundum-mullite composite ceramic roller rod. The present invention improves the performance by controlling the crystal form to improve the microstructure, ensures thermal stability and improves the overall strength of the roller rod; and improves the deviation of the roller rod size at both ends by combining large and small head conical blanks with hanging firing.

[0006] The technical problem to be solved by the present invention is also to provide a method for preparing a corundum-mullite composite ceramic roller, which is beneficial to improving the strength and thermal shock resistance of the ceramic roller.

[0007] In order to solve the above problems, the present invention provides a corundum-mullite composite ceramic roller, which comprises the following components in parts by weight:

[0008]

[0009] In some embodiments, the body of the ceramic roller is a hollow truncated cone.

[0010] In some embodiments, the taper of the hollow cone is (0.5-1.2):1000.

[0011] In some embodiments, the particle size of the alumina powder is 1 μm to 8 μm; the particle size of the corundum sand is 5 μm to 20 μm; the binder is one or more of polyvinyl alcohol, carboxymethyl cellulose, phenolic resin, hydroxypropyl methyl cellulose, and cyclodextrin; the crystal form control agent is one or more of vanadium pentoxide, boron oxide, cerium oxide, yttrium oxide, magnesium fluoride, and aluminum fluoride.

[0012] In some embodiments, the crystal form controlling agent is boron oxide and magnesium fluoride.

[0013] In some embodiments, the addition ratio of the boron oxide to magnesium fluoride is (1-2):1.

[0014] In order to solve the above problems, the present invention also provides a method for preparing a corundum-mullite composite ceramic roller, comprising the following steps:

[0015] Alumina micropowder, kaolin, corundum sand, a binder, a crystal control agent and water are mixed and ball-milled to obtain a primary mixture;

[0016] The primary mixed material is extruded through an extrusion device to obtain a green body;

[0017] The green body is subjected to a first drying treatment, cold isostatic pressing, drying and then sintering to obtain a finished product.

[0018] In some embodiments, the steps include:

[0019] Alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water are mixed and ball-milled to obtain a primary mixed mud;

[0020] The primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped green body;

[0021] The hollow truncated cone-shaped green body is placed in a preset mold after a first drying process for cold isostatic pressing, dried, and then sintered to obtain a finished product.

[0022] In some embodiments, the drying temperature of the first drying treatment is 50° C. to 120° C., and the insulation time is 24 h to 48 h.

[0023] In some embodiments, the pressure of cold isostatic pressing is 190 MPa to 360 MPa, and the holding time is 1 min to 10 min;

[0024] The firing is carried out by hanging firing, and the firing system is as follows:

[0025] Heating to 1200℃~1300℃, heating rate is 100℃ / h~300℃ / h;

[0026] The temperature is raised to 1600°C to 1650°C at a rate of 40°C / h to 45°C / h;

[0027] Raise the temperature to 1650℃~1800℃ at a rate of 40℃ / h~45℃ / h, and keep warm at 1650℃~1800℃ for 24h~48h.

[0028] The implementation of the present invention has the following beneficial effects:

[0029] The corundum-mullite composite ceramic roller provided by the present invention improves the ratio of aluminum oxide and silicon oxide, is conducive to the transformation of mullite and improves the conversion rate, and adopts a crystal control agent to prevent abnormal grain growth, improve the conversion rate, and optimize the microstructure. The present invention improves the material conversion rate and promotes mullite transformation through a reasonable formula, which is conducive to improving the thermal shock resistance of the ceramic roller; by improving the strength of the ceramic roller, it is conducive to optimizing the structure of the ceramic roller, reducing the thickness of the tube wall, and according to the material size effect, the thin wall is conducive to improving the thermal shock resistance of the product, and in addition, it achieves cost reduction and efficiency improvement; improving the thermal shock resistance of the product can extend the service life of the ceramic roller, reduce equipment maintenance costs, improve production efficiency and reduce production costs.

[0030] The invention provides a method for preparing a corundum-mullite composite ceramic roller rod. The invention adopts a method of combining extrusion and cold isostatic pressing to improve the density of the green body and thus improve the strength of the product. By improving the drying process, the drying uniformity of the green body is improved, which is beneficial to improving the overall strength and the yield rate. A specific firing technology process is adopted to fully carry out the primary mullite transformation and the secondary mullite transformation, thereby improving the strength of the ceramic roller rod and helping to improve the kiln transfer capacity and production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The figure is a schematic structural diagram of the green body of the corundum-mullite composite ceramic roller provided by the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. In addition, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0033] In the description of the present invention, it is necessary to understand that the terms "length", "width", "up", "down", "left", "right", "horizontal", "top", "bottom", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0035] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0036] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0037] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the examples of various specific processes and materials provided by the present invention, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.

[0038] In the present invention, "preferred" and "better" are only used to describe implementation methods or embodiments with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features. In the present invention, when involving numerical ranges, unless otherwise specified, the two endpoints of the numerical range are included.

[0039] The present invention provides a corundum-mullite composite ceramic roller, which comprises the following components in parts by weight:

[0040]

[0041] The corundum-mullite composite ceramic roller provided by the present invention improves the ratio of aluminum oxide and silicon oxide, is conducive to the transformation of mullite and improves the conversion rate, and adopts a crystal control agent to prevent abnormal grain growth, improve the conversion rate, and optimize the microstructure. The present invention improves the material conversion rate and promotes mullite transformation through a reasonable formula, which is conducive to improving the thermal shock resistance of the ceramic roller; by improving the strength of the ceramic roller, it is conducive to optimizing the structure of the ceramic roller, reducing the thickness of the tube wall, and according to the material size effect, the thin wall is conducive to improving the thermal shock resistance of the product, and in addition, it achieves cost reduction and efficiency improvement; improving the thermal shock resistance of the product can extend the service life of the ceramic roller, reduce equipment maintenance costs, improve production efficiency and reduce production costs.

[0042] In some embodiments, the particle size of the alumina powder is 1 μm to 8 μm; exemplary weight portions of the alumina powder are 35 parts, 40 parts, 45 parts, 50 parts, and 55 parts, not limited to the above. Exemplary weight portions of kaolin are 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, and 35 parts, not limited to the above. Preferably, the weight ratio of the alumina powder to the kaolin is (4 to 5): (3 to 4). The present invention improves the ratio of alumina to silicon oxide, facilitates the transformation of mullite, and increases the conversion rate of mullite, thereby facilitating the improvement of the strength of the ceramic roller, thereby facilitating the bending strength of the thin wall of the variable diameter ceramic roller, and enhancing the stability of the variable diameter ceramic roller in a high temperature environment, and reducing cracking or damage caused by thermal stress caused by rapid temperature changes.

[0043] In some embodiments, the particle size of the corundum sand is 5 μm to 20 μm; exemplary weight portions of the corundum sand are 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, and 35 parts, not limited to the above. Adding an appropriate amount of corundum sand can improve the mechanical strength of the variable diameter ceramic roller, enable it to withstand greater pressure and load, reduce thermal stress caused by temperature changes, and reduce the risk of cracking of the roller due to thermal shock, thereby extending the service life.

[0044] In some embodiments, the binder is one or more of polyvinyl alcohol, carboxymethyl cellulose, phenolic resin, hydroxypropyl methyl cellulose, and cyclodextrin; exemplary weight portions of the binder are 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, and 14 parts, but are not limited to the above. The binder can penetrate into the gaps between raw material particles such as corundum sand and mullite to enhance the bonding force between the particles.

[0045] In some embodiments, the crystal form control agent is one or more of vanadium pentoxide, boron oxide, cerium oxide, yttrium oxide, magnesium fluoride, and aluminum fluoride. Exemplary weight portions of the crystal form control agent are 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, and 5.5 parts, but are not limited to the above. The crystal form control agent is used to prevent abnormal grain growth, so that the microstructure of the roller can be more uniform, and its mechanical properties and thermal stability can be improved.

[0046] In some embodiments, Figure 1As shown, the body of the ceramic roller is a hollow truncated cone. Preferably, the taper of the hollow truncated cone is (0.5-1.2): 1000. Too large a taper of the hollow truncated cone will affect the use of the roller. The hollow truncated cone-shaped body 1 is made by extrusion molding. During extrusion molding, large and small head cones are obtained. The friction between the extruded body and the supporting groove is utilized. As the length of the body increases, the resistance of extrusion also increases slowly, causing the diameter of the body to slowly increase. In this way, large and small head cone bodies appear, that is, hollow truncated cone-shaped bodies 1. It should be noted that when sintering is performed by hanging firing, due to uneven fire control and temperature differences, the roller has a large head and a small tail. The present invention adopts large and small head conical bodies, and the large head is used for the tail of the small head. After hanging firing, the problem of large head and small tail can be reversely offset, so that a roller with uniform diameter can be achieved.

[0047] Furthermore, during the high-temperature firing process of the hollow truncated cone-shaped ceramic roller, the roller is subjected to inconsistent heating and stress in all directions due to its irregular shape, which causes the roller to shrink in all directions during the high-temperature firing process and the shrinkage of each part is inconsistent, resulting in the product size of the ceramic roller being unqualified. In some embodiments, the crystal form control agent is boron oxide and magnesium fluoride. Among them, the addition of an appropriate amount of magnesium fluoride can reduce the shrinkage rate of the hollow truncated cone-shaped ceramic roller, and the introduction of magnesium fluoride can also promote the sintering process of the hollow truncated cone-shaped ceramic roller, so that the hollow truncated cone-shaped ceramic roller can reach a higher density at a lower temperature, which helps to reduce the shrinkage difference caused by inconsistent sintering temperature. Boron oxide, as a strong flux, can significantly reduce the liquidus temperature of the hollow truncated cone-shaped ceramic roller batching system, thereby accelerating the melting process. This helps the hollow truncated cone-shaped ceramic roller to reach a stable state faster during the firing process and reduce the inconsistent shrinkage caused by uneven melting. Magnesium fluoride and boron oxide are used together. Magnesium fluoride mainly inhibits shrinkage and promotes sintering, while boron oxide optimizes the firing process of hollow frustum-shaped ceramic rollers by reducing the liquidus temperature and affecting the viscosity. The combined effect of the two makes the shrinkage of the hollow frustum-shaped ceramic rollers more uniform during the firing process, reducing the problem of inconsistent shrinkage in all directions.

[0048] In some embodiments, the addition ratio of the boron oxide to magnesium fluoride is (1-2): 1. Adding too much boron oxide will cause uneven grain growth of the ceramic and blur the grain boundary, thereby reducing the strength and toughness of the ceramic.

[0049] The present invention also proposes a corresponding preparation method, that is, a preparation method of a corundum-mullite composite ceramic roller, comprising the following steps:

[0050] (1) mixing alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water and then ball milling to obtain a primary mixture;

[0051] (2) the primary mixed material is extruded through an extrusion device to obtain a green body;

[0052] (3) The green body is subjected to a first drying treatment, cold isostatic pressing, drying and then sintering to obtain a finished product.

[0053] Preferably, the steps include:

[0054] (A) mixing alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water and then ball milling to obtain a primary mixed mud;

[0055] (B) the primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped body 1;

[0056] (C) After the first drying treatment, the hollow truncated cone-shaped green body 1 is placed in a preset mold for cold isostatic pressing, dried, and then sintered to obtain a finished product.

[0057] In some embodiments, the drying temperature of the first drying treatment is 50°C to 120°C, and the insulation time is 24h to 48h. Preferably, during the first drying treatment, a larger heating rate is used at a larger cross-sectional dimension of the hollow truncated cone-shaped blank 1, and a smaller heating rate is used at a smaller cross-sectional dimension of the hollow truncated cone-shaped blank 1. More preferably, the heating rate at a larger cross-sectional dimension of the hollow truncated cone-shaped blank 1 is 2°C / h to 3°C / h, and at a smaller cross-sectional dimension of the hollow truncated cone-shaped blank 1 is 1.0°C / h to 1.5°C / h. This can ensure the consistency of the drying of the hollow truncated cone-shaped blank 1.

[0058] In some embodiments, the cold isostatic pressing pressure is 190 MPa to 360 MPa, and the holding time is 1 min to 10 min. The above conditions are conducive to improving the density of the green body, thereby improving the mechanical strength of the roller.

[0059] In some embodiments, the firing is performed by hanging firing, and the firing system is:

[0060] Heating to 1200℃~1300℃, heating rate is 100℃ / h~300℃ / h;

[0061] The temperature is raised to 1600°C to 1650°C at a rate of 40°C / h to 45°C / h;

[0062] Raise the temperature to 1650℃~1800℃ at a rate of 40℃ / h~45℃ / h, and keep warm at 1650℃~1800℃ for 24h~48h.

[0063] The present invention adopts a specific firing technology process with a specific raw material formula to fully carry out the primary mullite transformation and the secondary mullite transformation, promote the conversion rate and mullite formation, and achieve high flexural strength and good thermal shock resistance of the ceramic roller. Moreover, when sintering by hanging firing, due to uneven fire control and temperature differences, the head of the roller is large and the tail is small. A conical blank with large and small heads is adopted, and the large head is used for the tail of the small head. After hanging firing, the problem of large head and small tail can be reversely offset, so that a roller with uniform diameter can be achieved. Furthermore, a suitable heating rate is adopted to avoid excessive internal stress of the ceramic caused by too fast a heating rate. In addition, a specific insulation time is adopted to ensure that the ceramic roller is completely densified, which is conducive to the ceramic roller having a more stable shrinkage rate, thereby ensuring that the product size of the ceramic roller is qualified.

[0064] The present invention is further described below with reference to specific embodiments.

[0065] Example 1

[0066] This embodiment provides a corundum-mullite composite ceramic roller, which includes the following components in parts by weight: 40g of aluminum oxide powder, 30g of kaolin, 30g of corundum sand, 10g of carboxymethyl cellulose, 2.5g of boron oxide and 2.5g of magnesium fluoride.

[0067] The body of the ceramic roller is a hollow frustum, and the taper of the hollow frustum is 1:1000.

[0068] The preparation method of the corundum-mullite composite ceramic roller in this embodiment comprises the following steps:

[0069] (A) mixing alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water and then ball milling to obtain a primary mixed mud;

[0070] (B) the primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped green body;

[0071] (C) After the first drying treatment, the hollow truncated cone-shaped green body is placed in a preset mold for cold isostatic pressing, dried, and then sintered to obtain a finished product.

[0072] The drying temperature of the first drying treatment is 100°C and the holding time is 36h; the pressure of the cold isostatic pressing is 240MPa and the holding time is 4min;

[0073] The firing system is:

[0074] Heating to 1250°C at a rate of 200°C / h;

[0075] Heating to 1600°C at a rate of 40°C / h;

[0076] Raise the temperature to 1700℃ at a rate of 40℃ / h and keep at 1700℃ for 24h.

[0077] Example 2

[0078] This embodiment provides a corundum-mullite composite ceramic roller, which includes the following components in parts by weight: 45g of aluminum oxide powder, 35g of kaolin, 35g of corundum sand, 15g of polyvinyl alcohol, 2g of boron oxide, and 2g of cerium oxide.

[0079] The body of the ceramic roller is a hollow frustum, and the taper of the hollow frustum is 0.5:1000.

[0080] The preparation method of the corundum-mullite composite ceramic roller in this embodiment comprises the following steps:

[0081] (A) mixing alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water and then ball milling to obtain a primary mixed mud;

[0082] (B) the primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped green body;

[0083] (C) After the first drying treatment, the hollow truncated cone-shaped green body is placed in a preset mold for cold isostatic pressing, dried, and then sintered to obtain a finished product.

[0084] The drying temperature of the first drying treatment is 100°C and the holding time is 38h; the pressure of the cold isostatic pressing is 240MPa and the holding time is 5min;

[0085] The firing system is:

[0086] Heating to 1250°C at a rate of 200°C / h;

[0087] Heating to 1600°C at a rate of 40°C / h;

[0088] Raise the temperature to 1700℃ at a rate of 40℃ / h and keep at 1700℃ for 24h.

[0089] Example 3

[0090] This embodiment provides a corundum-mullite composite ceramic roller, which includes the following components in parts by weight: 44 g of aluminum oxide powder, 37 g of kaolin, 28 g of corundum sand, 8 g of cyclodextrin, and 5 g of cerium oxide.

[0091] The body of the ceramic roller is a hollow frustum, and the taper of the hollow frustum is 1.2:1000.

[0092] The preparation method of the corundum-mullite composite ceramic roller in this embodiment comprises the following steps:

[0093] (A) mixing alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water and then ball milling to obtain a primary mixed mud;

[0094] (B) the primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped green body;

[0095] (C) After the first drying treatment, the hollow truncated cone-shaped green body is placed in a preset mold for cold isostatic pressing, dried, and then sintered to obtain a finished product.

[0096] The drying temperature of the first drying treatment is 120°C and the holding time is 20 hours; the pressure of the cold isostatic pressing is 240 MPa and the holding time is 5 minutes;

[0097] The firing system is:

[0098] Heating to 1300°C at a rate of 200°C / h;

[0099] Heating to 1650℃, heating rate is 40℃ / h;

[0100] Raise the temperature to 1800°C at a rate of 40°C / h and keep at 1800°C for 24h.

[0101] Example 4

[0102] The present embodiment provides a corundum-mullite composite ceramic roller, which includes the following components in parts by weight: 40 g of alumina powder, 30 g of kaolin, 30 g of corundum sand, 10 g of carboxymethyl cellulose, and 5 g of vanadium pentoxide.

[0103] The body of the ceramic roller is a hollow frustum, and the taper of the hollow frustum is 0.8:1000.

[0104] The preparation method of the corundum-mullite composite ceramic roller in this embodiment comprises the following steps:

[0105] (A) mixing alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water and then ball milling to obtain a primary mixed mud;

[0106] (B) the primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped green body;

[0107] (C) After the first drying treatment, the hollow truncated cone-shaped green body is placed in a preset mold for cold isostatic pressing, dried, and then sintered to obtain a finished product.

[0108] The drying temperature of the first drying treatment is 100°C and the holding time is 36h; the pressure of the cold isostatic pressing is 240MPa and the holding time is 4min;

[0109] The firing system is:

[0110] Heating to 1250°C at a rate of 200°C / h;

[0111] Heating to 1600°C at a rate of 40°C / h;

[0112] Raise the temperature to 1700℃ at a rate of 40℃ / h and keep at 1700℃ for 24h.

[0113] The performance of the ceramic rollers prepared in Examples 1 to 4 was tested. The bending strength was tested according to the national standard GB / T 6569-86, the apparent porosity of the ceramic roller was tested, and the thermal shock resistance was tested according to YB / T 376.2-1995. The test results are shown in Table 1.

[0114] Table 1 Performance of ceramic rollers prepared in Examples 1 to 4

[0115]

[0116] In the description of this specification, the description with reference to the terms "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0117] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A corundum-mullite composite ceramic roller, characterized in that: The ceramic roller comprises the following components in parts by weight:

2. The corundum-mullite composite ceramic roller according to claim 1, characterized in that: The body of the ceramic roller is a hollow truncated cone.

3. The corundum-mullite composite ceramic roller according to claim 1, characterized in that: The taper of the hollow cone is (0.5-1.2):1000.

4. The corundum-mullite composite ceramic roller according to claim 1, characterized in that: The particle size of the alumina powder is 1 μm to 8 μm; The particle size of the corundum sand is 5 μm to 20 μm; The binder is one or more of polyvinyl alcohol, carboxymethyl cellulose, phenolic resin, hydroxypropyl methyl cellulose, and cyclodextrin; The crystal form control agent is one or more of vanadium pentoxide, boron oxide, cerium oxide, yttrium oxide, magnesium fluoride, and aluminum fluoride.

5. The corundum-mullite composite ceramic roller according to claim 4, characterized in that: The crystal form controlling agents are boron oxide and magnesium fluoride.

6. The corundum-mullite composite ceramic roller according to claim 5, characterized in that: The addition ratio of the boron oxide and magnesium fluoride is (1-2):

1.

7. A method for preparing the corundum-mullite composite ceramic roller according to any one of claims 1 to 6, characterized in that: The following steps are involved: Alumina micropowder, kaolin, corundum sand, a binder, a crystal control agent and water are mixed and ball-milled to obtain a primary mixture; The primary mixed material is extruded through an extrusion device to obtain a green body; The green body is subjected to a first drying treatment, cold isostatic pressing, drying and then sintering to obtain a finished product.

8. The method for preparing the corundum-mullite composite ceramic roller according to claim 7, characterized in that: The following steps are involved: Alumina powder, kaolin, corundum sand, a binder, a crystal control agent and water are mixed and ball-milled to obtain a primary mixed mud; The primary mixed mud material is extruded through a direct push mud extruder to obtain a hollow truncated cone-shaped green body; The hollow truncated cone-shaped green body is placed in a preset mold after a first drying process for cold isostatic pressing, dried, and then sintered to obtain a finished product.

9. The method for preparing the corundum-mullite composite ceramic roller according to claim 7 or 8, characterized in that: The drying temperature of the first drying treatment is 50° C. to 120° C., and the insulation time is 24 h to 48 h.

10. The method for preparing the corundum-mullite composite ceramic roller according to claim 7 or 8, characterized in that: The pressure of cold isostatic pressing is 190MPa~360MPa, and the holding time is 1min~10min; The firing is carried out by hanging firing, and the firing system is as follows: Heating to 1200℃~1300℃, heating rate is 100℃ / h~300℃ / h; The temperature is raised to 1600°C to 1650°C at a rate of 40°C / h to 45°C / h; Raise the temperature to 1650℃~1800℃ at a rate of 40℃ / h~45℃ / h, and keep warm at 1650℃~1800℃ for 24h~48h.

Citation Information

Patent Citations

  • Corrosion-resistant ceramic roller and preparation method thereof

    CN110002859A

  • Low-shrinkage high-temperature-resistant aluminum oxide material as well as preparation method and application thereof

    CN115028436A

  • Ceramic slurry and preparation method of porous ceramic atomizing core

    CN115650762A

  • Ceramic roller and preparation method and application thereof

    CN118459208A

  • Composite for high-strength ceramic ware and manufacturing method of high-strength ceramic ware using the composite

    KR1020120057857A

Cited By

  • Alkali-free aluminum oxide ceramic for spark plug insulator and preparation method of alkali-free aluminum oxide ceramic

    CN122380813A